ADAPTING PEDAGOGY: EXAMINING TEACHERS' PERSPECTIVES ON ZOOM FOR CULTIVATING SPEAKING PROFICIENCY IN FORUM KAMPUNG BAHASA (FKB) - Zainal Asgaf, La Ode; Irma Khairany Mumtaza (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2023)
This study aims to investigate teachers' perspectives on using Zoom in teaching speaking. The research design of this study was a descriptive quantitative study. The participants under investigation in this study comprises the entirety of teachers at Forum Kampung Bahasa (FKB) Pare, estimated to be approximately 300 individuals. The data collection method was a questionnaire consisting of 24 items. The result shows that the teachers were reported to have high perception on the use of Zoom. Most of the teachers or 85.3% of the teachers in this current research were categorized into high category, and there were 24 teachers or 14.1% from the total of the teachers belonging to medium category. There were only 0.6% of teachers who perceived low perception. The teachers’ perceptions toward the use of Zoom in each aspect were categorized as good based on the mean score (basic knowledge concept = 3.96; readiness= 4.18 easiness= 4.09; benefits= 4.13)